RISK FACTORS OF ANAEMIA AMONG ZIDOVUDINE-BASED REGIMEN IN PATIENTS WITH HIV INFECTION- A COHORT STUDY - Ramalingam Pullipalayam Kandaswamy; Radha, Devarajan; Karunanithi, Gayathri; Gaur , Archana; Geetha, Jeganathan; Sindhura, Gajula; Sakthivadivel, Varatharajan (Journal of Ayub Medical College Abbottabad, 2023)
Background: Anaemia in patients with HIV infection is commonly multifactorial in origin. Nutritional deficiencies and the presence of opportunistic infections as well as HIV infection itself can cause anaemia. HIV medications like zidovudine can also cause anaemia in patients with HIV infection. This study aimed to study the prevalence and risk factors of anaemia in patients with HIV infection on a zidovudine-based HAART regimen. Methods: This hospital-based prospective cohort study was done at the ART (anti-retroviral therapy) centre. All adult patients with HIV attending the ART centre were included in the study. After obtaining written informed consent, the patient’s demographic data, risk factors, WHO staging, and body mass index (BMI) were noted. Study population was divided into two groups as patients with or without anaemia and compared using appropriate statistical tests. Results: Out of the 202 patients with HIV infection on a zidovudine-based regimen, 52 patients (25.7%) developed anaemia. Anaemia was common in stage 3 or stage 4 of WHO staging (OR-9.94, CI-3.89-25.36) and in patients with low CD4 counts (OR-0.988, CI-0. 982-0.995). Patients with anaemia had significant opportunistic infections. Conclusion: Anaemia is common in patients with HIV on zidovudine-based HAART regimen, which is seen as early as less than 8 weeks. WHO staging, and CD4 count were the primary risk factors for anaemia, which a change of treatment regimen and supportive measures can reverse.